Responses of teachers in Scotland to the reintroduction of the practical project in the advanced higher chemistry curriculum - Traynor Erin; Scott Fraser J.; Thomson Patrick I. T. (Chemistry Teacher International)
Many pupils who study chemistry in Scotland and intend to progress to university undertake a final capstone practical research project as part of their Advanced Higher chemistry qualification. This project work was suspended for several years due to COVID-19, then reintroduced in 2023/24. We surveyed 47 Scottish teachers during this first project year using a mixed-methods survey, and found that resource availability had the biggest impact on projects, with over half of respondents reporting that they asked pupils to buy materials and a third committing their own money. Technician support was seen as critical to success, but project selection was heavily curtailed by the availability of existing equipment or chemicals, even as teachers made good use of available professional development and other forms of support. We finally make recommendations around the resourcing of project work and teacher/technician CPD provision.